2021
DOI: 10.1093/eurheartj/ehab250
|View full text |Cite
|
Sign up to set email alerts
|

Accelerometer-derived physical activity and risk of atrial fibrillation

Abstract: Aims Physical activity may be an important modifiable risk factor for atrial fibrillation (AF), but associations have been variable and generally based on self-reported activity. Methods and results We analysed 93 669 participants of the UK Biobank prospective cohort study without prevalent AF who wore a wrist-based accelerometer for 1 week. We categorized whether measured activity met the standard recommendations of the Euro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
41
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(58 citation statements)
references
References 46 publications
4
41
1
Order By: Relevance
“…Third, nearly all the included studies assessed selfreported PA exposure, which might be prone to recall bias and overestimation. However, a recently published article showed an inverse association between PA and AF by using accelerometer measurements (51), which confirms our main results. Specifically, they found a weak correlation between accelerometer assessment and self-reported PA and a nonsignificant AF benefit from self-reported exercise.…”
Section: Strengths and Limitationssupporting
confidence: 92%
“…Third, nearly all the included studies assessed selfreported PA exposure, which might be prone to recall bias and overestimation. However, a recently published article showed an inverse association between PA and AF by using accelerometer measurements (51), which confirms our main results. Specifically, they found a weak correlation between accelerometer assessment and self-reported PA and a nonsignificant AF benefit from self-reported exercise.…”
Section: Strengths and Limitationssupporting
confidence: 92%
“…However, HF was not included as an outcome. 30 Several studies have examined device-measured PA and overall CVD risk by intensity but not in HF. Contrary to our results, a study showed that VPA, but not MPA or LPA, was associated with a lower risk of stroke.…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
“…A separate LOOP analysis assessed physical activity measured through the loop recorder showing that a 1 h reduction in average daily physical activity was associated with an increased odds of AF onset the next day by ≈25%, 24 a finding supported by a recent UK Biobank analysis using a wrist-based accellerometer. 25 These data strengthen the evolving links between modifiable risk factors, physical activity, and AF providing a foundation for new tools to evaluate and intervene in lifestyle modification programmes. 26 …”
Section: Randomized Controlled Trials In Atrial Fibrillation With or ...mentioning
confidence: 63%
“… 7 Stopping consuming alcohol after detection of AF may reduce stroke; 5 it may also reduce the recurrence of AF after ablation. 6 Less AF 24 , 25 and stroke 25 was also seen with higher levels of physical activity (PA) as measured by modern day monitoring technology (#) in LOOP trial 24 and UK Biobank. 25 Also from the UK Biobank: long-term night shift work may cause AF.…”
mentioning
confidence: 99%
See 1 more Smart Citation